A ANTI-INFLAMMATORY EFFECT OF MATOA LEAF ETHANOL EXTRACT (Pometia pinnata J.R Forst & G. Forst) IN MALE RATS (Rattus norvegicus) - FITRI NUR AWALIYAH FAHMI (Makassar Natural Product Journal (MNPJ), 2023)
Inflammation is the body's normal response to injury or tissue damage which is characterized by heat (calor), pain (dolor), swelling (tumor) and redness (rubor). Matoa leaves contain flavonoid compounds which have anti-inflammatory properties. The purpose of this study was to determine the effect anti-inflammatory of the ethanol extract of matoa leaves (Pometia Pinnata J.R Forst & G. Forst) in male rats (Rattus norvegicus). This study used 25 rat test animals which were divided into 5 treatment groups, group I negative control in the form of 1% Na CMC suspension, group II positive control in the form of diclofenac sodium suspension, groups III, IV and V were given a suspension of ethanol extract of matoa leaves with concentrations of 200 mg/kgBB, 400 mg/kgBB and 800 mg/kgBB. Measurements were made every 1 hour after administration of a comparison or test extract for 6 hours and then recorded. The results showed that the ethanol extract of matoa leaves had the potential as an anti-inflammatory candidate with the most effective dose in reducing the volume and diameter of edema was a dose of 400 mg/kgBB.